Immature teratoma of kidney in a 5-month-old child - Adhikari, RC; Sayami, G (Journal of Pathology of Nepal, 2013)
We report a rare case of immature renal teratoma in a 5-month-old female infant. The patient presented with abdominal mass, which was found to arise from the left kidney. The preoperative diagnosis of Wilms’ tumor was based on clinical and imaging findings. The patient was managed with nephrectomy and had normal recovery. The histopathological examination of nephrectomy specimen revealed grade 2 immature teratoma. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 425-527 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7875